2015
DOI: 10.5152/tjg.2014.6990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a kefir supplement on symptoms, colonic transit, and bowel satisfaction score in patients with chronic constipation: A pilot study

Abstract: Background/Aims: Although probiotics have been extensively studied in irritable bowel syndrome, data on the impact of probiotics on chronic constipation are scarce. We aimed to evaluate the effects of kefir, which is a probiotic fermented milk product, on the symptoms, colonic transit, and bowel satisfaction scores of patients with chronic constipation. Materials and Methods: Twenty consecutive patients with functional constipation according to the Rome II criteria were divided into two groups based on their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
2
22
0
8
Order By: Relevance
“…It was found that GE administration could be reduced in three participants owing to kefir’s probiotic effect (Ino et al ). Similar findings also were observed among patients in Turkey (Turan, Dedeli, Bor, & Ilter, ). The current study investigated the effects of kefir on constipation among all the individuals who were hospitalized in Beppu Developmental Medical Center in order to determine whether including kefir in dietary regimens could reduce the administration of aperients to some individuals with constipation.…”
Section: Introductionsupporting
confidence: 84%
“…It was found that GE administration could be reduced in three participants owing to kefir’s probiotic effect (Ino et al ). Similar findings also were observed among patients in Turkey (Turan, Dedeli, Bor, & Ilter, ). The current study investigated the effects of kefir on constipation among all the individuals who were hospitalized in Beppu Developmental Medical Center in order to determine whether including kefir in dietary regimens could reduce the administration of aperients to some individuals with constipation.…”
Section: Introductionsupporting
confidence: 84%
“…ere has been growing evidence suggesting that probiotics, or at least specific probiotic strains, may have a beneficial role in alleviating constipation symptoms [9,10]. Interestingly, functional foods, such as probiotic-containing dairy products, have been introduced as treatment options for constipation and showed favorable effects [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…HT-29-NF-κB-hrGFP clon E5 cells were cultured in RPMI1640 medium and supplemented with 10% (v/v) FBS. Cells were routinely propagated in 25 or 75 cm 2 tissue culture flasks at 37ºC, 5% CO 2 in a humidified incubator until reaching approximately 70% confluence [24]. Subsequently, cells were trypsinized and concentration was adjusted for different experimental settings.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…Among bacteria, Lactobacilli and Bifidobacteria are the main genera of probiotics which have been implicated in beneficial outcomes. Probiotics can exert health benefits for treatment and prevention of gastrointestinal disorders, such as impairment of colonic transit, enteric infections and post-antibiotic syndrome, reduction of recurrence of Clostridium difficile associated diarrhea, prevention of necrotizing enterocolitis and colorectal cancer, and prevention and treatment of inflammatory bowel diseases [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%